FAKTOR – FAKTOR YANG MEMPENGARUHI RENTABILITAS PERBANKAN DI INDONESIA (Studi Pada Bank Yang Terdaftar Di Bank Indonesia Periode 2010-2012) (Students' Journal of Accounting and Banking, 2015)
This research aim to analyzed the rentabilities of the commercial and conventional banks in Indonesia with the purpose to determine the influence exerted by the variable Loan to Depossit Ratio, Non-Performing Loans and Equity on Return On Assetsat the Commercial and Conventional Banks listed in Bank Indonesia. The population of this study were 145 commercialand conventional banks listed in Bank Indonesia, where the entire population by using purposive sampling technique reduced to59 banks. Multiple linear regression analysis techniques used to determine the influence between variables which is the purpose of this study. The research show that simultaneously Loan to Depossit Ratio, Non-Performing Loans and Equity have significanteffect on the amount of Return On Assetswith a determination equal to 45.6%. The results of partial analysis proves that the variable Loan to Depossit Ratio and Equity have a positive and significant effect on Return on Assets, while the variable Non-Performing Loans has a significant and negative effect on Return on Assets. Based on these results it can be concluded that the Return On Assetswill increase along with the increase that occurred in the Loan to Depossit Ratio and equity, while the increase in Return On Assetswill also occur when non-performing loans declined.Keywords: Loan to Depossit Ratio, Non Performing Loan, Ekuitas, Return On Assets